Social-based routing in pocket switched networks - AOJiu-xin C; HENGao-jun C; ANGJing Y; HUZi-qing Z; IUBo L (Tongxin xuebao)
In pocket switched network,how to make effective balance between the message delivery ratio and transmis-sion delay is a problem to be solved.A community-based PSN routing algorithm,named BridgingCom,is proposed.It uses local community detection method with aging mechanism and introduces the bridging centrality as the basis of for-warding decisions.The algorithm combines the analysis of node centrality with the structure of social mobile network,makes full use of the community relationship and activeness of nodes in PSN.Simulation results show that BridgingCom routing algorithm has better performance in the message delivery ratio and message average delay compared to a number of previously proposed algorithms.